Advances in pediatrics in 2023: choices in allergy, analgesia, cardiology, endocrinology, gastroenterology, genetics, global health, hematology, infectious diseases, neonatology, neurology, pulmonology - Carlo Caffarelli; Francesca Santamaria; Elena Bozzola; Bertrand Tchana; Ettore Piro; Enrico Vito Buono; Daniela Cunico; Raffaele Cerchione; Alessandro Dorato; Cristina Fontanella; Sergio Bernasconi; Giovanni Corsello (Italian Journal of Pediatrics)
Abstract In the last year, there have been many remarkable articles published in the Italian Journal of Pediatrics. This review highlights papers that can be potentially helpful in healthcare practice among the most cited or accessed papers on the journal website. We have chosen key articles on allergy, analgesics, cardiology, endocrinology, gastroenterology, genetics, global health, infectious diseases, neonatology, neurology and pulmonology. Advances in understanding risk factors, mechanisms, diagnosis, treatment options and prevention of pediatric diseases have been discussed and in the context of the subsequent steps. We think that progresses achieved in 2023 will have a significant impact on the management of diseases in childhood.